2018
DOI: 10.1101/474452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-Cancer Repository of Validated Natural and Cryptic mRNA Splicing Mutations

Abstract: We present a major public resource of mRNA splicing mutations validated according to multiple lines of evidence of abnormal gene expression. Likely mutations present in all tumor types reported in the Cancer Genome Atlas (TCGA) were identified based on the comparative strengths of splice sites in tumor versus normal genomes and then validated by respectively comparing counts of splice junction spanning and abundance of transcript reads in RNA-Seq data from matched tissues and tumors lacking these mutations.The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Exon-based expression microarrays and q-RT-PCR techniques were initially used to confirm the predicted impact of common and rare SNPs on splicing. Results were subsequently confirmed using RNAseq data for some of these SNPs Dorman et al 2014, Shirley et al 2019. However, exon skipping due to rs1893592 was not consistently seen in all carriers.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Exon-based expression microarrays and q-RT-PCR techniques were initially used to confirm the predicted impact of common and rare SNPs on splicing. Results were subsequently confirmed using RNAseq data for some of these SNPs Dorman et al 2014, Shirley et al 2019. However, exon skipping due to rs1893592 was not consistently seen in all carriers.…”
Section: Discussionmentioning
confidence: 81%
“…The extent to which SNP-related sequence variation accounts for the heterogeneity in mRNA transcript structures has been somewhat unappreciated, given the relatively high proportion of genes that exhibit tissue-specific alternative splicing Pan et al 2008;Baralle et al 2017). This and our previous study (Shirley et al 2019) raise questions regarding the degree to which apparent alternative splicing is the result of genomic polymorphism rather than splicing regulation alone. Because much of the information required for splice site recognition resides within neighboring introns, it would be prudent to consider contributions from intronic and exonic polymorphism that produce structural mRNA variation, since these changes might be associated with disease or predisposition.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…42 Shirley et al showed that 341 486 variants had a significant impact on mRNA splicing, and approximately 70% of these variants were not registered in the dbSNP database. 43,44 Furthermore, these studies could analyze all genes and identify novel splicing variants because of integrated analyses using raw sequence data such as FASTQ or BAM files. In studies using TCGA datasets, one of the things to be considered is how to handle data from normal samples because tumor matched normal samples are a lot fewer than only tumor samples in TCGA.…”
Section: Discussionmentioning
confidence: 99%